Contextual Representation of Mourning Rituals: A Case Study of Rural Punjab (Pakistan) (Journal of Asian Development Studies, 2024)
This study is conducted to explore the mourning rituals performed in the rural area of Punjab Pakistan. Specifically, the research focusses on the dynamics between culture and death rituals signified through different religio-cultural practices. The qualitative methods are used employing ethnographic research design. To analyze the data, the thematic analysis technique is used. The study found that the people in rural areas of Punjab perform different rituals on death to show their emotions and intensity of grief. The results show that people in this area practice rituals following their religious and cultural beliefs to please the soul of the deceased as well as to show their reaction towards grief. The findings of this study reveal that wailing, crying, cutting one's body and burning the stick of sage are a few of the mourning rituals that are commonly prevalent in rural Punjab to express grief. Moreover, different folklores are also sung to dialogue the departed soul with other community members and God, which is a great source of attention seeking for showing massive grief. Nature of death and economic disparity is also played a major role while expressing the grief. Generally, the bereaved families use such rituals to get an escape from the grief. To sum up the study found that the death rituals to express and share individuals’ grief are decline in the culture of rural Punjab.